Metals Immobilization of Coal Fly Ash and Bottom Ash-Based Geopolymers - Himawan T.B.M. Petrus; Brilian R. Sadewo; Handika M. Prabu; Shelia F. Hunarko; Ferian Anggara (Jurnal Teknik Kimia Indonesia, 2022)
Indonesian government through Presidential Decree No. 22 year 2017 determines the energy supply management to result 135.5 GW at which coal possess 30% of the national energy consumption until the year of 2025. In 2019 approximately 162,2 tons millions coal will be used as fuel and approximately 8,31 million tons coal ash which consist of fly ash and bottom ash produced from coal fired power plant. Coal fly ash waste will increase up to 14 million tons per year in 2050 due to government plan to build 430,000 Megawatt power plant with 107,500 Megawatts of power projects will be contributed by Coal-fired Steam Power Plant. Coal fly ash waste has negative impact to the health of human and environment due to its heavy metal oxide that potentially release through the environment. Along with the concept of green utilization technology, coal ash could utilize as concrete materials. Fly ash and bottom ash can be combined to create geopolymer concrete. Geopolymer concrete making involves a polymerization process occurring between the alkali activators in combination of sodium hydroxide and water glass with Si – Al minerals resulting three - dimensional polymeric chain. Experimental studies were conducted to test the resistance of geopolymer bonds to immobilize of heavy metals on geopolymer concrete. Two types of geopolymer concrete samples were used with fly ash: bottom ash ratio of 9:1 and 1:1. The sample was immersed into a solution of sulfuric acid solution pH 1, sodium hydroxide pH 12, sea water and aquadest. XRD, SEM-EDS, XRF, EDX and compressive strength tests were performed on liquid and solid samples. It was found that the 9:1 concrete composition has higher compressive strength than 1:1. The result of the compressive strength test shows that 41%; 21%; 27% and 10% reduction when it immersed in sulfuric acid, sodium hydroxide, sea water, aquadest respectively. The reduction of compressive strength due to leached metal elements that contribute to the strength. This research aims that geopolymer concrete can be utilized as a construction material in extreme environment, such as geothermal area, sea and oil rig.